2015
DOI: 10.1089/scd.2014.0284
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Perturbed CXCL12 Signal Processing: Analyses of Immature Hematopoiesis in GRK6-Deficient Mice

Abstract: Hematopoietic stem and progenitor cells (HSPCs) reside in bone marrow (BM) in an environment rich in CXCL12, the ligand for CXCR4, which is constitutively expressed on all immature hematopoietic cells in BM. This ligand-receptor pair critically controls HSPC retention and (relative) quiescence in BM. Interestingly, in a chemokine-abundant environment, CXCR4 surface expression and CXCL12 sensitivity of BM-residing HSPCs are continuously maintained. The mechanisms underlying this peculiar pattern of G-protein si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…CXCL12 is a cytokine that is essential for stem cell quiescence. It is produced and secreted by many different stromal cell types, especially CXCL12-abundant reticular (CAR) cells near the endosteum or sinusoidal endothelial cells and promotes normal hematopoiesis [ 51 , 56 , 57 , 58 ].Cell surface, membrane-bound via heparin sulfate CXCL12 is essential for stem cell quiescence, retention, and self-renewal when presented by the BM stroma [ 56 , 57 , 59 , 60 ]. On its secretion and release to the peripheral blood, it induces active stem and progenitor cell migration and mobilization that elevated by ROS, JNK, MMP9, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL12 is a cytokine that is essential for stem cell quiescence. It is produced and secreted by many different stromal cell types, especially CXCL12-abundant reticular (CAR) cells near the endosteum or sinusoidal endothelial cells and promotes normal hematopoiesis [ 51 , 56 , 57 , 58 ].Cell surface, membrane-bound via heparin sulfate CXCL12 is essential for stem cell quiescence, retention, and self-renewal when presented by the BM stroma [ 56 , 57 , 59 , 60 ]. On its secretion and release to the peripheral blood, it induces active stem and progenitor cell migration and mobilization that elevated by ROS, JNK, MMP9, etc.…”
Section: Introductionmentioning
confidence: 99%
“…RANTES induces expression of promyeloid transcription factors including Gata 2 which is important for the maintenance and expansion of multipotent progenitors and HSCs and reduces expression of lymphoid-specification genes including Ikaros and Gata3 which is shown to regulate early lymphopoiesis and T-cell development. Moreover, RANTES activates mTOR and its downstream target proteins such as P16, P19 and P21which lead to HSCs senescence [ 58 , 67 ]. Notably, those multiple factors mentioned above have innumerous pathways involved in hematopoiesis, stem cell mobilization, and immune system modulation, hence the regulation relationship among them may be complicated because of the pleiotropic effects in a specialized niche environment.…”
Section: Introductionmentioning
confidence: 99%
“…13, 14 GRK6 knockout (GRK6 −/− ) mice show increased severity of acute inflammatory arthritis 15 and colitis 16 because of enhanced granulocyte chemotaxis, and develop autoimmune diseases due to impaired macrophage engulfment. 17 GRK6 regulates chemotaxis through SDF/CXCLs-CXCR4, 18, 19 leukotriene B4-induced CGRP receptor 20 and BLT receptor 21 activation. Moreover, It has been reported that the expression and activity of GRK6 change during differentiation of the promyelocytic cell line HL-60, 22 suggesting the potential involvement of GRK6 in earlier leukocyte development.…”
mentioning
confidence: 99%
“…GRK6 is specifically expressed in lymphoid tissues and myeloma, and is absent from or weakly expressed in most primary human somatic tissues; it is similarly expressed in mice (12). The SDF-1/CXCR4 axis (13), and the HSP90 and STAT3 signaling pathway (14-16) play significant roles in MM. Recent studies have shown that GRK6 is involved in many kinds of cell signaling (17).…”
Section: Discussionmentioning
confidence: 99%